Evaluation Of The Flipped Learning Program In Improving Students' English Proficiency At Lembaga Bahasa LIA Cibinong - Rhinomuraena Murtoaji Abikusno; Sri Sundari; Auderey G. D. Tangkudung; Marisi Pakpahan; Rudianto Rudianto (International Forum of Researchers and Lecturers, 2024)
This study analyzesthe effectiveness of the flipped learning program in enhancing the English language proficiency of students at LembagaBahasa LIA Cibinong. Using a descriptive qualitative approach, the study adopts the Kirkpatrick evaluation model, which includes four aspects: student reactions, the learning process, behavior change, and the final outcomes of the program implementation. Data were collected through observation, interviews, and documentation, and analyzed through stages of condensation, presentation, and conclusion drawing. The subjects of the study involved the branch manager, academic staff, instructors, as well as students from LIA Cibinong and Jalan Baru, with the study being conducted from May to July 2024. The results of the study show that the implementation of flipped learning received positive feedback from students, increased active participation in class discussions, and developed critical thinking skills. Students also reported improvements in their English skills, particularly in speaking, listening, and vocabulary acquisition. Although challenges such as self-motivation and technological limitations still exist, the program has proven effective in enhancing the quality of learning and students' social skills. Classroom observation evaluations confirmed a consistent improvement in students' language skills. Additionally, the program had a positive impact on the institution's business growth. In conclusion, flipped learning has been shown to be an effective method and is worth further development atLembaga Bahasa LIA Cibinong. Recommendations for further development include optimizing learning motivation through gamification, improving the quality of materials, enhancing facilities, and providing additional training for teachers to maximize the potential of this method.